(untitled) (Research, Society and Development, 2020)
The endometriosis is an estrogen-dependent inflammatory disorder, characterized by the exacerbated growth of endometrial tissue and stromal cells outside the uterine cavity. The quality of life is decreased in women with endometriosis, mainly with the worsening of symptoms. Because of the importance of endometriosis for public health, this article aimed to explain the pathophysiology of endometriosis, the forms of diagnosis and treatment, as well as the implications of the disease on female fertility and forms of treatment through assisted reproduction. To this end, 50 Portuguese and English references dated between the years 2014 to 2020 were selected as a priority. The etiology of endometriosis is complex, surrounded by several theories, and early diagnosis is crucial to minimize damage to fertility since 30 to 50% of women with endometriosis exhibit infertility. Several complications are observed in patients affected by the pathology that leads to infertility. To maintain female fertility, assisted reproduction techniques have been used successfully. In conclusion, for the maintenance of the quality of life and female fertility, the early diagnosis of endometriosis is essential. Moreover, assisted reproduction techniques emerge as the most successful treatment line for women suffering from endometriosis who wish to become pregnant.